2020
DOI: 10.1007/s11837-020-04324-z
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Rich Intermetallic Formation and Mechanical Properties of Recycled AA6111 Alloy Strips Produced by Melt Conditioning Twin Roll Casting

Abstract: The impact of high shear melt conditioning on the morphology and distribution of Fe intermetallic compounds was investigated in the processing of recycled AA6111 alloy by the twin roll casting process. The optical and scanning electron microscope (SEM) micrograph studies were carried out on twin roll casting (TRC) and melt conditioning twin roll casting (MC-TRC) samples. The microstructural analysis showed fine and uniformly distributed Fe-rich intermetallic phases for MC-TRC strips compared with the TRC strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…wt.% Mn β-AlFeSi plate-like phase decreased from 34 (±11) µm in the reference material to 20 (±4) µm in the processed material, which agrees with previous studies[15].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…wt.% Mn β-AlFeSi plate-like phase decreased from 34 (±11) µm in the reference material to 20 (±4) µm in the processed material, which agrees with previous studies[15].…”
supporting
confidence: 93%
“…It can be applied to casting processes, such as direct chill casting and twin roll casting [14]. It not only provides refinement and uniform distribution of the matrix and the Fe-rich phases [15], but also efficient degassing [16] and enhanced de-ironing [17], which has a significant effect on the reduction in microstructural defects and the improvement in tensile properties of the recycled aluminum alloy [15,18].…”
Section: Introductionmentioning
confidence: 99%
“…The properties show that there is variation in total elongation between higher and lower values for DC-GR and MC-DC cast up to 19% and 10%, respectively for the different orientations tested. This anisotropy is well known for aluminum alloys sheets [ 26 ]. Okayasu et al [ 27 ] found that the anisotropic microstructure that formed during sheet rolling control the mechanical properties of aluminum alloy sheets.…”
Section: Resultsmentioning
confidence: 92%
“…However, due to the various sources of Al scraps and use of iron-based tools, these impurity elements, such as, Fe and Si, are easily introduced to the recycled Al alloys [6] , [7] , [8] , [9] . Fe is the main impurity element in Al-Cu alloys, that form hard and brittle plate-like Fe-rich intermetallic phases (named Fe-rich phases hereinafter) during solidification [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] . The type of Fe-rich phases in Al-Cu alloys, such as, Al 3 (CuFe), Al 6 (CuFe), Al 7 Cu 2 Fe (β-Fe), Al 15 Fe 3 (SiCu) 2 (α-Fe), varies with different alloy compositions, cooling rates, and external fields during solidification [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%